The rs75862629 minor allele in the endoplasmic reticulum aminopeptidases intergenic region affects human leucocyte antigen B27 expression and protects from ankylosing spondylitis in Sardinia. (17th June 2019) - Paladini, Fabiana; Fiorillo, Maria Teresa; Tedeschi, Valentina; D'Otolo, Viviana; Piga, Matteo; Cauli, Alberto; Mathieu, Alessandro; Sorrentino, Rosa
Abstract: Objectives: HLA-B27 and the endoplasmic reticulum aminopeptidase 1 ( ERAP1 ) and ERAP2 genes are predisposing factors for AS. A single nucleotide polymorphism (SNP) in the ERAP2 promoter (rs75862629) coordinates the transcription of both ERAP genes. We investigated whether this SNP associates with AS and whether it affects the expression of the two major HLA-B27 alleles present in Sardinia, the AS-associated B*2705 and the non-AS-associated B*2709. Methods: Four SNPs in the ERAP region were genotyped in HLA-B*2705-positive patients with AS (n = 145), B27-positive healthy subjects (n = 126) and B27-negative controls (n = 250) and the allele and haplotype frequencies were derived. The expression of ERAP1 and ERAP2 mRNAs in 36 HLA-B27-positive B lymphoblastoid cell lines was measured by quantitative PCR. An electrophoretic mobility shift assay was performed to search for a nuclear factor binding the DNA sequence encompassing rs75862629. The expression of HLA-B27 molecules related to the SNP at rs75862629 was determined by flow cytometry. Results: The minor allele G at rs75862629 was found significantly increased in B27 healthy individuals, both B*2705 and B*2709, compared with B*2705-positive patients with AS and B27-negative controls. The electrophoretic mobility shift assay indicated the lack of binding of a transcription factor as the cause of the observed reduction in the ERAP2 concomitant with a higher ERAP1 expression. Of note, this occurs with a different cell surface expression of the HLA-B*2705 and HLA-B*2709 molecules. Conclusion: SNP rs75862629, by modulating simultaneously the expression of ERAP1 and ERAP2, provides protection from AS in HLA-B27-positive subjects in Sardinia. This has a functional impact on HLA-B27 expression and likely on disease onset.